Profil Daya Tahan Jantung Paru Pada Atlet Pra Pon Sulut Cabang Olahraga Futsal Putra Tahun 2023 - Igo Ariyanto Ginoga; Fentje W. Langitan; Maxi M.L. Moleong (STIKES Columbia Asia Medan, 2025)
This study aims to determine the profile of cardiorespiratory endurance among male futsal athletes participating in Pra PON SULUT 2023, as well as to analyze the variability in their cardiovascular performance. The research employs a descriptive quantitative approach, involving 35 athletes selected through total sampling. Measurements were conducted using the bleep test to assess cardiorespiratory endurance. The results indicate that 75% of the athletes fall within the